The paradox of collaborative governance in leprosy rehabilitation in Central Java - Al Hafis, Raden Imam; Warsono, Hardi; Larasati, Endang; Purnaweni, Hartuti (Management and Entrepreneurship: Trends of Development, 2021)
This research aims to observe and compare the ideal concept of collaborative governance and the implementation in the field related to the rehabilitation of leprosy patients in Central Java. For citizens who have physical limitations caused by an illness, the burden will be the responsibility of the government in meeting their needs. Solving these problems requires the government's political will and the involvement of cross-actor to be able to provide a more complex problem-solving color according to the collaborative governance model presented by Ansell & Gash. Methodology used in this research is qualitative. An in-depth interview approach was carried out in collecting data and information related to the paradox of the rehabilitation of leprosy patients in Jepara Regency, Central Java. The findings in this study indicate that there is no good collaboration between actors in the rehabilitation of leprosy patients and the throwing of responsibilities on institutions that should carry out rehabilitation. The recommendation suggested in this paper is that clear rules are needed and anyone who is involved in the rehabilitation program is needed, of course, by involving many institutions that are not only the hospital as the sole implementer in the rehabilitation of leprosy patients in Central Java. In addition, it is necessary to support adequate resources for the achievement of this program if it has been established and clear rules are made so that it does not interfere with the allocation of funds from each of the institutions involved.JEL Classification:  D73, I120, I180.